Body image in the workplace: Assessing the impact on self-esteem and employee engagement - Kevin S. Kertechian; Hadi El-Farr (Acta Psychologica, 2025)
This study investigates the relationship between body image and employee vigor in work engagement, with a focus on self-esteem as a mediating factor. Drawing on social comparison theory, we analyze survey data from 860 U.S. employees using structural equation modeling to assess the impact of positive and negative body image on employee vigor. The findings reveal that positive body image enhances employee vigor, while negative body image directly undermines it. Crucially, self-esteem mediates the negative body image-vigor link, underscoring its role in mitigating harmful effects. By introducing body image into management studies, this research bridges an important interdisciplinary gap, demonstrating its significance in workplace well-being and engagement. The study highlights the need for organizational interventions that foster positive body image and strengthen employee self-esteem to enhance employees' organizational outcomes. While our findings provide actionable insights, the research is limited to U.S. employees, and further exploration is warranted across diverse cultural contexts. Additionally, despite preventive measures, the cross-sectional design poses challenges in establishing causal relationships. Nonetheless, this study contributes to understanding how body image influences work engagement, urging organizations to address this often-overlooked factor in employee well-being strategies.